Black youth aspirations : imagined futures and transitions into adulthood - Maja, Botshabelo (Emerald Publishing Limited, 2021)
This book is about how to trigger the capacity to aspire among black youth. Examining the transition out of adulthood and imagined futures of black youth, Maja helps us understand how black youth aspirations might be raised, and how a better future for young people can be achieved. Black Youth Aspirations tracks the journeys of nine black teenagers in South Africa, and how they navigate their way through the final two years of schooling. Maja explores and discovers the maps of the future that youths envision, and investigates how their immediate environments in and out of school serve as instruments that help them interpret, navigate, and manifest those aspirations. Presenting a new conceptual tool, OATS (Objects, Agency, Tools, and Spaces), seeks to provide practical meaning on how to best develop young people's capacity to aspire. Filling it gap in the scholarly literature, and digging deeper than the statistics ever could, this book is a dynamic interaction between research among youth and the application of concepts to make sense of their stories. As the first book that discusses the aspirational pathways of working class black youth in the context of the global south, the theoretical and research approaches on which the book is based make it an exciting and novel addition to the global literature in the area of youth studies.